Vertically oriented MoS2/WS2 heterostructures on reduced graphene oxide sheets as electrocatalysts for hydrogen evolution reaction. (16th March 2021) - Lee, Hoon Ju; Lee, Suk Woo; Hwang, Hyuntae; Yoon, Seong In; Lee, Zonghoon; Shin, Hyeon Suk
Abstract : One pot synthesis of vertical MoS2 /WS2 heterostructures on reduced graphene oxide sheets (MoS2 /WS2 /rGO) showing high catalytic activity for HER. Abstract : Significant efforts in the catalytic applications of transition metal dichalcogenides (TMDs) have been made, primarily focused on the design and synthesis of their vertically aligned structures, including expanded interlayer spacing, to pursue the maximized exposure of active edge sites. However, vertically aligned TMD heterostructures are rare. In this work, we demonstrate vertical MoS2 /WS2 heterostructures on reduced graphene oxide sheets (MoS2 /WS2 /rGO) by a one-pot synthesis, which show a high catalytic activity for the hydrogen evolution reaction (HER). The vertically aligned heterostructures were characterized by Raman spectroscopy, transmission electron microscopy, and energy dispersion spectroscopy. Compared with MoS2 /rGO (with an onset potential of −125 mV and a Tafel slope of 81 mV dec −1 ), MoS2 /WS2 /rGO exhibited a much enhanced electrochemical HER performance with an onset potential of −113 mV and a Tafel slope of 44 mV dec −1 . The electrochemical impedance results suggest that the enhanced catalytic activity of MoS2 /WS2 /rGO can be attributed to fast electron transfer in the TMD heterostructure. This work suggests great potential for TMD-based (photo)electrocatalysts through modification of their morphology and interlayer spacing.